If \( \sin x + \sin^2 x = 1 \), \( x \in \left(0, \frac{\pi}{2} \right) \), then the expression
\[
(\cos^2 x + \tan^2 x) + 3(\cos^4 x + \tan^4 x + \cos^4 x + \tan^4 x) + (\cos^6 x + \tan^6 x)
\]
is equal to:
Show Hint
For trigonometric identities, converting all terms into sine and cosine often simplifies the calculation effectively.
Step 1: Understanding the given identity.
Given \( \sin x + \sin^2 x = 1 \), we have:
\[
\sin x = \cos^2 x \quad \Rightarrow \quad \tan x = \cos x
\]
Step 2: Expanding the given expression.
The given expression becomes:
\[
2\cos^2 x + [\cos^6 x + \cos^3 x] + 2\cos^6 x
\]
\[
= 2[\sin^2 x + \sin^3 x + \sin^4 x]
\]
\[
= 2\sin^2 x [( \sin x + 1 )^2]
\]
\[
= 2[\sin^2 x + \sin^3 x] = 2
\]